Splenic artery aneurysms: About two cases treated successfully - Ormaechea, Carlos; Praderi, Raul; Gomez Fossati, Carlos (Cirugía del Uruguay, 1971)
The author presents two cases ( the 6th and 7th in national case material) of aneurism of the splenic artery. One was asymptomatic, calcified and was a fortuitious finding in a radiological intraoperatory study made during a reoperation of the biliary tract. The other one, broxen in free peritoneum appeared as an massive hemoperitoneum, in a young patient with a history of malaria. The clinical, diagnostica!, ethiopathogenic and therapeutic aspects are discussed.